2013
DOI: 10.1021/jz4010637
|View full text |Cite
|
Sign up to set email alerts
|

Terminal Oxygens in Amorphous TeO2

Abstract: Understanding the structure of single-component glasses is essential for developing structural models of more complex multicomponent glasses. Currently, such models for tellurite systems are purely qualitative. This study presents neutron diffraction and Raman spectroscopy measurements of the structure of pure amorphous TeO 2 , showing that it is formed from a combination of two-thirds [TeO 4 ] pseudo-trigonal bipyramids and onethird [TeO 3 ] trigonal pyramids with a terminal oxygen. This is in contrast to all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
96
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 97 publications
(109 citation statements)
references
References 39 publications
13
96
0
Order By: Relevance
“…showed that there is a step-change in and PQ at about 15 mol% Na2O, close to the composition where a change in Te environment is proposed by our structural model for tellurites [19]. By means of an empirical relation derived by Koller et al, [38] they used their values of to estimate the average coordination number of sodium in their sodium tellurite glasses, giving nNaO = 5.8 and 5.5 for the glasses containing 10 and 20 mol% Na2O respectively.…”
Section: Na Magic Angle Spinning Nmrsupporting
confidence: 79%
See 4 more Smart Citations
“…showed that there is a step-change in and PQ at about 15 mol% Na2O, close to the composition where a change in Te environment is proposed by our structural model for tellurites [19]. By means of an empirical relation derived by Koller et al, [38] they used their values of to estimate the average coordination number of sodium in their sodium tellurite glasses, giving nNaO = 5.8 and 5.5 for the glasses containing 10 and 20 mol% Na2O respectively.…”
Section: Na Magic Angle Spinning Nmrsupporting
confidence: 79%
“…The total correlation functions, (Figure 4), exhibit two peak maxima at ~1.9 and 2.8 Å, which may be assigned to Te-O bonds and O…O distances respectively and thus arise from the Te-O network. It is important to note that the distribution of Te-O bond lengths in tellurite glasses [19] extends over a wide range of interatomic distances (say ~1.8 -2.4 Å). The expected positions for the M-O contributions to are indicated by arrows in Figure 4;…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations